Nanostructured ZnO as a structural template for the growth of ZIF-8 with tunable hierarchical porosity for CO2 conversion. Issue 29 (27th January 2017) - Kim, Min-Kyeong; Kim, Daeok; Seo, Jung Yoon; Buyukcakir, Onur; Coskun, Ali
Abstract : We report a new approach to introduce hierarchical porosity into ZIF-8 by using three-dimensional nanostructured porous ZnO as a structural template. Abstract : We report a new approach to introduce hierarchical porosity into ZIF-8 by using three-dimensional nanostructured porous ZnO as a structural template. Importantly, the textural properties of these nanostructures can be tuned simply by varying the size of the polymeric templates used for the preparation of ZnO. Moreover, the growth of ZIF-8 crystals on ZnO and the resulting hierarchical porosity enabled enhanced catalytic activity for the conversion of CO2 into cyclic carbonates through an atom economy reaction in high yields with exceptional product selectivity.